2018
DOI: 10.1186/s12913-018-2959-3
|View full text |Cite
|
Sign up to set email alerts
|

Community mobilization and maternal Care of Women Living with HIV in poor settings: the case of Mfuwe, Zambia

Abstract: BackgroundResearch has shown that community mobilization is a useful strategy in promoting maternal care of HIV negative women in resource poor settings; however, similar evidence for women living with HIV is missing. Therefore, in this study we provide this evidence by exploring the relevance of community mobilization in the promotion of maternal health care among women living with HIV in resource-poor settings by using Mfuwe, a rural district in Zambia as a case study.MethodsBy relying on Focus Group Discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
3
13
0
Order By: Relevance
“…This is because in this way, TBAs cannot be monitored, regulated nor given further training. This may have worsened the quality of services offered by TBAs much to the detriment of local women [6, 10]. This observation is in line with what other scholars have continued to show elsewhere within SSA [1519].…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…This is because in this way, TBAs cannot be monitored, regulated nor given further training. This may have worsened the quality of services offered by TBAs much to the detriment of local women [6, 10]. This observation is in line with what other scholars have continued to show elsewhere within SSA [1519].…”
Section: Discussionsupporting
confidence: 68%
“…Out of necessity, women continued to covertly utilize them as they were the only feasible option. Our respondents including other studies from Mfuwe [10, 14] confirm that despite the ban, women continue to utilize services of TBAs out of necessity. TBAs continue to operate illegally making any possibilities of improving their potential benefits and minimizing their limitations impossible.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Further, the HIV response has mainly focused on formal responses with little focus on the role played by community support systems despite them being the most widely used by people on the ground given the weak health system in conflict regions [ 5 , 6 ]. In particular, indigenous social relations that help promote opportunities for care and support among internally displaced people (IDPs) with HIV [ 7 , 8 ]. Research has shown that in SSA, formal interventions only carry a small proportion of the burden; the bulk of the burden is carried by the communities in which the HIV-infected live their daily lives [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%